Elegy to Narcissus - Antich, Peter (Stance: an international undergraduate philosophy journal, 2019)
This poem is a musing on the thought of Heraclitus. The central opposition I reflect from Heraclitus’ fragments is sleep and wakefulness. This opposition is encountered throughout the fragments as the opposition between life and death, vision and darkness, and wisdom and ignorance.